2021
DOI: 10.3390/antib10030034
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemistry-Based Diagnosis of Extrapulmonary Tuberculosis: A Strategy for Large-Scale Production of MPT64-Antibodies for Use in the MPT64 Antigen Detection Test

Abstract: Tuberculosis (TB) is a global health problem. The immunohistochemistry (IHC)-based MPT64 antigen detection test has shown promising results for diagnosing extrapulmonary TB in previous studies. However, the anti-MPT64 antibody currently used in the test is in limited supply, and reproduction of a functional antibody is a prerequisite for further large-scale use. Various antigen-adjuvant combinations and immunisation protocols were tested in mice and rabbits to generate monoclonal and polyclonal antibodies. Ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In all previous studies, we used an in‐house polyclonal antibody which was available in limited amounts. With the intention for scale‐up of the test, we reproduced the primary antibody and produced a single batch of this new polyclonal antibody in large amounts [ 21 ]. Since polyclonal antibodies recognize and bind to different epitopes of the antigen in question, the performance of the reproduced primary antibodies may differ from those previously used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In all previous studies, we used an in‐house polyclonal antibody which was available in limited amounts. With the intention for scale‐up of the test, we reproduced the primary antibody and produced a single batch of this new polyclonal antibody in large amounts [ 21 ]. Since polyclonal antibodies recognize and bind to different epitopes of the antigen in question, the performance of the reproduced primary antibodies may differ from those previously used.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologists (MRP, MK, and SI) were trained in immunostaining and slide evaluation. The production of the anti‐MPT64 antibodies used in our study is described in detail by Hoel et al [ 21 ]. In brief, rabbits were immunized to produce polyclonal anti‐MPT64 antibodies, and the performance of various adjuvants–antigen combinations was assessed by IHC screening using serial dilutions to identify the optimal working dilution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secreted Mtb antigens have been identified via IHC staining in Mtb-infected human lung tissue (7)(8)(9)(10)(11). Similarly, we used IHC to detect Mtb secreted antigen 85B (Ag85B) in the same pulmonary and testicular specimens used for RNAscope analysis (Figures 2, 3).…”
Section: Mtb Mrna and Secreted Antigens Accumulate In The Cytoplasm O...mentioning
confidence: 99%
“…In vitro and in vivo studies have shown that several secreted Mtb antigens are present within TB lesions (6). Despite the potential of using antibodies to detect Mtb surface or secreted antigens (7)(8)(9)(10)(11), little progress has been made to improve TB diagnostics beyond ZN staining. Whereas mRNA-based diagnostic tests have been proposed for TB (12), studies comparing RNA in situ hybridization (RISH) methods with routine histochemistry and/or immunohistochemistry (IHC) for the spatial identification of Mtb are lacking, especially in paucibacillary and abacillary tissues.…”
Section: Introductionmentioning
confidence: 99%